Using the company’s reserves to employ its social responsibility: A comparative analytical study - Latif, Adnan Baqi; Azad, Handren (Journal of Legal and Political Studies, 2024)
The concept of the company's contribution to assuming social responsibility in the environment in which it carries out its activity imposes on companies the necessity of allocating part of the saved reserve from annual net profits and directing it to non-profit activities with the aim of contributing to bearing public costs as part of their duties towards society and their contribution to comprehensive development. Since bearing this responsibility clashes with the basic purpose of corporate activity, which is the intention of achieving profits and distributing them to shareholders, therefore, allocating the company’s funds for the purposes of carrying out its social responsibility requires not violating the law or the company’s contract or system, which requires those in charge of managing the company to use means that with legal cover to avoid the company from lawsuits by shareholders or its creditors. It is noteworthy, in this context, that the Iraqi legislator is unique - among comparative laws - in explicitly stipulating in the amended Companies Law No. (21) of 1997 that companies are obligated to perform their social responsibilities through the company’s reserve. However, there are several problems surrounding this position, so this came The comparative analytical study to address these problems by proposing mechanisms for monitoring and implementing this responsibility and explaining the penalty that may result from the company due to failure to fulfill this obligation, as well as ways to limit companies’ evasion of performing their social responsibility.
Keywords: Use of company reserves,Social responsibility,Company funds